Analysis of Shallot Farming Business in Pringsewu Regency - Maryusuf Achmad; Fitriani Fitriani; Henry Kurniawan (Journal of The Community Development in Asia, 2024)
Shallot farming in Pringsewu Regency, Indonesia, is a profitable business with an average income of IDR 298 million per hectare. However, the productivity is still low, at 15 tons/ha compared to the potential of 20 tons/ha. This research analyzes the cost structure, production, income, and income of shallot farming in Pringsewu Regency. The research results show that the total cost is IDR 115 million per hectare, while the average income is IDR 182 million per hectare. The feasibility analysis shows that shallot farming is profitable with an R/C ratio of 2.6 and a B/C ratio of 1. To improve the performance of shallot cultivation in Pringsewu and Pagelaran Districts, important suggestions involve providing proactive mentoring and advice from the Food Crops Agriculture Service, facilitated by PPL officers. Furthermore, farmers should explore the adoption of advanced shallot farming techniques to increase income. Additionally, it is recommended to extend the duration of shallot cultivation, supported by favorable returns on investment, as indicated by Internal Rate of Return (IRR) values of 97% and 93% for two planting periods in Pagelaran District, exceeding the bank interest rate of 12%. In summary, increasing productivity can further increase the profitability of shallot farming in Pringsewu Regency